2008
DOI: 10.1248/bpb.31.2316
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Topical Microemulsion of Capsaicin Free of Surfactant

Abstract: Capsaicin (8-methyl N-vanillyl-6 nonenamide), an active compound extracted from Chilli peppers, is widely used for treatment of rheumatoid arthritis, osteoarthritis, diabetic neuropathy and postherpetic neuralgia. 1) However, first pass effect of capsaicin is very high, 2) and the half-life of capsaicin after intravenous administration is only 7.06 min in rats 3) and 12.44 min in rabbits. 4) Adverse events of capsaicin mainly include burning, stinging and erythema at the application site. 5) Topical applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Apparently, cubosomes could conserve a sustained release profile for Cl. The initial fast release rate attributed to free Cl on the cubosome particle surface, while drug incorporated into the particle core has been released in a prolonged mode (Zhang et al, 2008, Zhuang et al, 2010). In addition, GMO as a basic cubosomes component might lead to decreasing the drug partitioning rate from the oily medium to the aqueous one when compared to the pure drug which could diffuse easily to the dissolution media (Nguyen et al, 2017, Patil et al, 2015, Sadanshio et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, cubosomes could conserve a sustained release profile for Cl. The initial fast release rate attributed to free Cl on the cubosome particle surface, while drug incorporated into the particle core has been released in a prolonged mode (Zhang et al, 2008, Zhuang et al, 2010). In addition, GMO as a basic cubosomes component might lead to decreasing the drug partitioning rate from the oily medium to the aqueous one when compared to the pure drug which could diffuse easily to the dissolution media (Nguyen et al, 2017, Patil et al, 2015, Sadanshio et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The permeation rate of capsaicin at steady state, through the rat skin was calculated by linear regression. 31 , 32 …”
Section: Methodsmentioning
confidence: 99%
“…Capsaicin can release substance P from the afferent nociceptive neurons, and the resulting depletion of substance P desensitizes small afferent sensory neurons. 14) However, orally administered capsaicin undergoes significant first-pass metabolism in rats and mice, 15) and the spiciness of capsaicin limits its clinical applications. Several current studies have reported the topical and transdermal delivery of capsaicin using novel carriers, e.g., niosomes or ME, but these formulations remain limited by their high concentration of capsaicin (0.75% (w/w)) 9) and the use of high levels of ethanol or benzyl alcohol.…”
mentioning
confidence: 99%